PENGARUH HERBAL THERAPY COMPRESS BALL TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH IBU INPARTU KALA 1 DI KLINIK PRATAMA SITI KHOLIJAH HASIBUAN KECAMATAN MARELAN - Sari, Husna; Hayati, Erlina; Krisna, Putri; Saradilla, Wira (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
The pain you feel is closely related to the birthing process. Various efforts have been made to reduce discomfort during childbirth, both by pharmacological and non-pharmacological methods. One way to reduce maternal pain during childbirth is by non-pharmacological methods such as using herbal therapy compress balls. This ball utilizes heat conduction to increase blood flow to painful areas, while its analgesic effect comes from the herbal ingredients and essential oils it contains. Aromatherapy has a calming and soothing effect. This research aims to find out how herbal compress ball therapy can help reduce back pain in mothers in the early stages of labor. To measure the level of muscle pain is an observation sheet equipped with the Wong-Baker FACES Rating Scale, which divides muscle pain into five categories: no pain, mild pain, moderate pain, controlled severe pain, and controlled severe pain. This research is a quasi-experimental research with one group using pre-test and post-test methods. The number of samples used was 20 people using purposive sampling. Data were analyzed using the Wilcoxon test with a p value of 0.000 (p<0.05). In 2024, the Siti Kholijah Hasibuan Pratama Clinic will show that administering herbal therapy compression balls has significant benefits in reducing low back pain in early postpartum mothers.